Inflammatory Response of Ischemic Tolerance in Circulating Plasma: Preconditioning-Induced by Transient Ischemic Attack (TIA) Phenomena in Acute Ischemia Patients (AIS) - Colàs-Campàs, Laura; Farre, Joan; Mauri-Capdevila, Gerard; Molina-Seguín, Jessica; Aymerich, Núria; Ois, Ángel; Roquer, Jaume; Tur, Silvia; García-Carreira, María del Carmen; Martí-Fàbregas, Joan; Cruz-Culebras, Antonio; Segura, Tomás; et al. (Frontiers in Neurology, 2020)
Introduction. Ischemic tolerance (IT) refers to a state where cells are resistant to the damaging effects caused by periods of ischemia. In a clinical scenario, IT phenomenon is activated by a recent transient ischemic attack (TIA) before an ischemic stroke (IS). The dissection of inflammatory protein expression patterns would contribute to better understand IT. Methods. A total of 477 IS patients from nine hospitals, recruited between January 2011 and January 2016, were included in the current study and divided in three groups: 438 (91.9%) patients without previous TIA(group 1), 22 (4.6%) patients who suffered TIA 24 hours before IS (group 2), and 17 (3.5%) patients who suffered TIA between 24 hours and 7 days prior to IS (group 3). An inflammatory biomarker panel (IL-6, NT-proBNP, hsCRP, hs-Troponin, NSE and S-100b) on plasma and a cytokine antibody array was performed to achieve the preconditioning signature potentially induced by TIA phenomena. Primary outcome was modified rankin scale (mRs) score at 90 days. Results. Recent previous TIA was associated with better clinical outcome at 90 days (median mRS of group 1: 2.0 [1.0-4.0]; group 2: 2.0[0.0-3.0]; group 3 1.0[0-2.5]; p=0.086) and smaller brain lesion (group 1: 3.7 [0.7-18.3]; group 2: 0.8 [0.3-8.9]; group 3: 0.6 [0.1-5.5] mL; p=0.006). All inflammation biomarkers were down regulated in the groups of recent TIA prior to IS compared to those who did not suffer a TIA event,..Moreover, a cytokine antibody array revealed 30 differentially expressed proteins between the three groups. Among them, HRG1-alpha (Fold change 74.4 between group 1 and 2; 74.2 between group 1 and 3) and MAC-1 (Fold change 0.05 between group 1 and 2; 0.06 between group 1 and 3) expression levels would better stratify patients with TIA 7 days before IS. These two proteins showed an earlier inflammation profile that was not detectable by the biomarker panel. Conclusion. Inflammatory pathways were activated by transient ischemic attack, however the period of time between this event and a further ischemic stroke could be determined by a protein signature that would contribute to define the role of ischemic tolerance induced by TIA.